2004
DOI: 10.1023/b:inte.0000031740.85124.78
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Optic Nerve Head Neovascularization in Proliferative Diabetic Retinopathy After Intravitreal Triamcinolone Regression of Diabetic Optic Disc Neovascularization After Intravitreal Triamcinolone

Abstract: The aim of this study is to report the clinical outcome of a diabetic patient with optic nerve head neovascularization treated with an intravitreal injection of triamcinolone acetonide. A 52-year-old patient presented with clinically significant diffuse macular edema and optic nerve head neovascularization due to proliferative diabetic retinopathy in her right eye. Despite grid laser photocoagulation in the macular region macular edema progressed and visual acuity declined. The patient received a single intrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 5 publications
0
12
0
1
Order By: Relevance
“…For decades, studies have suggested that IVTA may be useful to temporarily increase visual acuity in patients with diffuse DME [18,19,21,22,23,24,25,26,27,28,29,30,31,32,33,34]. The most convincing evidence came from a prospective, double-masked, placebo-controlled and randomized trial by Sutter et al [34].…”
Section: Clinical Studies: Ta As Drug Treatment For Macular Edemamentioning
confidence: 99%
See 1 more Smart Citation
“…For decades, studies have suggested that IVTA may be useful to temporarily increase visual acuity in patients with diffuse DME [18,19,21,22,23,24,25,26,27,28,29,30,31,32,33,34]. The most convincing evidence came from a prospective, double-masked, placebo-controlled and randomized trial by Sutter et al [34].…”
Section: Clinical Studies: Ta As Drug Treatment For Macular Edemamentioning
confidence: 99%
“…Robert Machemer and colleagues in particular thought about intravitreal triamcinolone acetonide (IVTA) as a therapy of proliferative vitreoretinopathy [1,3,4,9,13,14,15,16]. As a consequence of Machemer’s suggestion, IVTA has been used for the treatment of other intraocular proliferative, edematous and neovascular diseases such as proliferative diabetic retinopathy [17,18], diffuse diabetic macular edema (DME) and diabetic retinopathy in general [18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79], branch retinal vein occlusion (BRVO) [80,81,82,83,84,85,86,87,88,89,90,91,92], central retinal vein occlusion (CRVO) […”
Section: Introductionmentioning
confidence: 99%
“…In a similar manner, Zacks and Johnson [51] concluded that combination treatment of panretinal laser coagulation and intravitreal triamcinolone acetonide may provide benefit in patients with diffuse diabetic macular edema who require urgent laser treatment for proliferative diabetic retinopathy by preventing an exacerbation of macular edema. Karacorlu et al [30] reported on the clinical outcome of a patient with proliferative diabetic retinopathy and diabetic macular edema which progressed despite grid laser photocoagulation in the macular region. After a single intravitreal injection of 4 mg triamcinolone acetonide, visual acuity increased, macular edema decreased, and neovascularization of the optic nerve head markedly regressed.…”
Section: Diabetic Macular Edema and Proliferative Diabetic Retinopathmentioning
confidence: 99%
“…This approach can be useful to prevent the exacerbation of the macular oedema, however it will not treat pre-existing macular oedema. Intravitreal triamcinolone acetonide (TA) has been shown to be clinically effective in cases of intraocular inflammatory, oedematous, neovascular and proliferative disorders [11][12][13][14]. With reference to these effects, TA usage in the treatment of concomitant non-high-risk PDR and diffuse CSMO is reasonable.…”
Section: Introductionmentioning
confidence: 99%